- two *x*(x + one)/(x^ two - four)^ two + one /(x^ two - four) = zero
minus 2 multiply by x multiply by (x plus 1) divide by (x squared minus 4) squared plus 1 divide by (x squared minus 4) equally 0
minus two multiply by x multiply by (x plus one) divide by (x to the power of two minus four) to the power of two plus one divide by (x to the power of two minus four) equally zero
-2*x*(x + 1)/(x2 - 4)2 + 1/(x2 - 4) = 0
-2*x*x + 1/x2 - 42 + 1/x2 - 4 = 0
-2*x*(x + 1)/(x² - 4)² + 1/(x² - 4) = 0
-2*x*(x + 1)/(x to the power of 2 - 4) to the power of 2 + 1/(x to the power of 2 - 4) = 0
-2x(x + 1)/(x^2 - 4)^2 + 1/(x^2 - 4) = 0
-2x(x + 1)/(x2 - 4)2 + 1/(x2 - 4) = 0
-2xx + 1/x2 - 42 + 1/x2 - 4 = 0
-2xx + 1/x^2 - 4^2 + 1/x^2 - 4 = 0
-2*x*(x + 1) divide by (x^2 - 4)^2 + 1 divide by (x^2 - 4) = 0